2015
DOI: 10.1002/adma.201502110
|View full text |Cite
|
Sign up to set email alerts
|

A Large‐Bandgap Conjugated Polymer for Versatile Photovoltaic Applications with High Performance

Abstract: A new copolymer PM6 based on fluorothienyl-substituted benzodithiophene is synthesized and characterized. The inverted polymer solar cells based on PM6 exhibit excellent performance with Voc of 0.98 V and power conversion efficiency (PCE) of 9.2% for a thin-film thickness of 75 nm. Furthermore, the single-junction semitransparent device shows a high PCE of 5.7%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
725
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,014 publications
(739 citation statements)
references
References 75 publications
11
725
0
3
Order By: Relevance
“…WBG polymers can be synthesized by using moderate electron‐donating and electron‐withdrawing D–A pairs 10, 11, 12, 13, 14, 15, 16. For instance, Sun and co‐workers showed a successful example of poly{dithieno[2,3‐ d :2′,3′‐ d′ ]benzo[1,2‐ b :4,5‐ b′ ]dithiophene‐ co ‐1,3‐bis(thiophen‐2‐yl)‐benzo‐[1,2‐ c :4,5‐ c′ ]dithiophene‐4,8‐dione} (PDBT‐T1), which has a bandgap of 1.85 eV and a high PCE of 9.7%.…”
Section: Introductionmentioning
confidence: 99%
“…WBG polymers can be synthesized by using moderate electron‐donating and electron‐withdrawing D–A pairs 10, 11, 12, 13, 14, 15, 16. For instance, Sun and co‐workers showed a successful example of poly{dithieno[2,3‐ d :2′,3′‐ d′ ]benzo[1,2‐ b :4,5‐ b′ ]dithiophene‐ co ‐1,3‐bis(thiophen‐2‐yl)‐benzo‐[1,2‐ c :4,5‐ c′ ]dithiophene‐4,8‐dione} (PDBT‐T1), which has a bandgap of 1.85 eV and a high PCE of 9.7%.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] During the last decade, remarkable progress has been made in enhancing the power conversion efficiency (PCE) of the PSCs, such as development of high-performance polymer donors, [4][5][6][7][8][9][10][11][12][13][14] incorporation of efficient interfacial materials, [15][16][17] and advancement of device architectures. [1][2][3][4] During the last decade, remarkable progress has been made in enhancing the power conversion efficiency (PCE) of the PSCs, such as development of high-performance polymer donors, [4][5][6][7][8][9][10][11][12][13][14] incorporation of efficient interfacial materials, [15][16][17] and advancement of device architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Designing new conjugated polymers and delving into the relationship between structure and properties to improving PCE and device stability seem still necessary. [12][13][14] Huo et al reported a polymer based on a BDF core, named PBDF-T1, symmetric structure, less attention has been paid on the asymmetric structures. Simultaneously, donor materials should possess basic features: (1) Broad and strong absorption band in the visible and near-infrared region to match well with solar spectrum; (2) low-lying HOMO energy level for assuring a high open-circuit voltage (V oc ); (3) a coplanar molecular structure and good crystalline properties to enhance charge transport for a high fill factor (FF); (4) excellent solubility for solution process.…”
mentioning
confidence: 99%
“…[12][13][14] Huo et al reported a polymer based on a BDF core, named PBDF-T1, symmetric structure, less attention has been paid on the asymmetric structures. 13,25 Generally, fluorine-containing polymer has a relatively high V oc in contrast to the non-fluorinated one. 4,19 For example, thieno [3,4-b]thiophene (TT) unit, coupled with alkythienyl-substituted BDT (PTB7-Th) in a regiorandom pattern as the electron donor material demonstrated a fairly satisfying PCE over 10% and isoindigo (ID) unit, copolymerization with dithienocarbazole (P(IID1F-DTC)) also presented a high PCE of 7.1%.…”
mentioning
confidence: 99%